Citizenship and democracy: Achievements and debts - Guzmán León, Juany (2011)
The purpose of these notes is to highlight certain discussion and analysis elements regarding citizenship as a concept that currently permeates decision-making processes in democratic societies. Increasingly, the ‘legitimacy’ of governments and public policies hinges on the exercise of so-called active citizenship, and the individual and organized participation of residents—who are simultaneously subjects and objects of decision-making processes and the recognition of rights and opportunities. This challenge carries particular weight in Central America, which navigates this dual aspiration of democratic development and expanded citizenship under constraints.